Structure-activity relationship of 1-desamino-8-D-arginine vasopressin as an antiproliferative agent on human vasopressin V2 receptor-expressing cancer cells - Pastrian, María Belén (2014)
The synthetic nonapeptide 1-desamino-8-D-arginine vasopressin (dDAVP) can reduce tumor cell growth through agonist action on the vasopressin V2 receptor. A structure-antiproliferative activity relationship analysis of dDAVP was performed using the alanine scanning technique on the aggressive MDA-MB-231 human breast carcinoma cell line. The results from this analysis demonstrated that the amino acids located at the loop of dDAVP are important for the antiproliferative activity of dDAVP, highlighting the key role of the N-terminal region of the peptide in the interaction with the tumor cell surface receptor. The findings from this study present novel strategies for designing improved compounds with enhanced stability for cancer therapy.